2018
DOI: 10.1038/s41374-018-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6 secreted by bone marrow mesenchymal stem cells attenuates intervertebral disc degeneration by inhibiting the TLR2/NF-κB signaling pathway

Abstract: Inflammation has been correlated with intervertebral disc degeneration (IDD). Recent evidence suggests that TNF-α-stimulated gene 6 protein (TSG-6) secreted by bone marrow mesenchymal stem cells (BMSCs) displays a remarkable ability to inhibit inflammatory processes in a variety of diseases. However, it is unknown whether BMSCs exert their therapeutic effect against IDD by secreting TSG-6. Here we investigated the effects of BMSCs and TSG-6 on IDD and explored the possible underlying mechanisms in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…Previous studies have shown that BMSCs can secrete TSG-6 to modulate the inflammatory microenvironment partly by inhibiting the activation of the TLR2/NF-κB signaling pathway [40,41]. Recently, we also proved that TSG-6 secreted by BMSCs can delay or even prevent intervertebral disc degeneration partly by suppressing the activation of the TLR2/MyD88/NF-κB signaling pathway in nucleus pulposus cells [27]. However, whether TSG-6 secreted by BMSCs exerts an anti-nociceptive effect in neuropathic pain by directly inhibiting the activation of the TLR2/ MyD88/NF-κB signaling pathway in spinal dorsal horn microglia remains unclear.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Previous studies have shown that BMSCs can secrete TSG-6 to modulate the inflammatory microenvironment partly by inhibiting the activation of the TLR2/NF-κB signaling pathway [40,41]. Recently, we also proved that TSG-6 secreted by BMSCs can delay or even prevent intervertebral disc degeneration partly by suppressing the activation of the TLR2/MyD88/NF-κB signaling pathway in nucleus pulposus cells [27]. However, whether TSG-6 secreted by BMSCs exerts an anti-nociceptive effect in neuropathic pain by directly inhibiting the activation of the TLR2/ MyD88/NF-κB signaling pathway in spinal dorsal horn microglia remains unclear.…”
Section: Introductionmentioning
confidence: 73%
“…Isolation, culture, and identification of BMSCs SD rat primary BMSCs were prepared as previously described [27]. Briefly, primary BMSCs were obtained from the bone marrow of the tibias and femurs of 4-week-old male SD rats under aseptic conditions.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can reverse liver fibrosis and ameliorate liver damage in mice. Furthermore, TSG-6 plays a role in the treatment of autoimmune diseases (22,23).…”
Section: Introductionmentioning
confidence: 99%